Amy had $24.80 more than Beatty at first. After Beatty gave $14.20 to Amy,

Amy had 3 times as much money as Beatty in the end. How much did Beatty have at first?

Let Beatty = x - $ 14.20
Amy = 3 (x- $14.20)
= 3x - $43
So far is my equations correct? Not sure what to do next, please help!
Many thanks

3 answers

what happened to the $24.80 difference at the start?
If Betty started with x, then
Amy started with x+24.80
After the donation of 14.20,
Amy had x+24.80+14.20
Betty had x - 14.20
So now you have
x+24.80+14.20 = 3(x-14.20)
I think you'll find this works out better.
Once you have an answer, check it to make sure it works for the stated conditions. You did not do this. The first clue would be that 43/3 does not divide evenly into dollars and cents.
x + $40 = 3x - $43
x = $83
SUBS
$83+24.80+14.20 = 3($83-14.20)
122 does not equal to 207
Sorry I'm confused, please explain
Beatty has $(X - 14.20).
Amy has $(x+24.80) + 14.20.

(x+24.80) + 14.20 = 3(x-14.20).
x + 39 = 3x - 42.60
X = $40,80 = Amt. Beatty had at first.